Kualitas Pelayanan Izin Penyelenggaraan Satuan Pendidikan Swasta Melalui Aplikasi Cerdas Layanan Perizinan Terpadu Untuk Publik (SiCantik Cloud) di Kabupaten Gresik - Purnamasari, Anggun Cahaya; Eprilianto, Deby Febriyan (Universitas Negeri Surabaya, 2024)
The rapid development of technology requires agencies to be able to provide practical services, in this case the government seeks modernization of services through e-government. E-government implemented by DPMPTSP Gresik Regency is SiCantik Cloud. However, in its implementation, there are still several obstacles, namely applications that often error, slow loading and cannot download permits that have been issued on user accounts. From these obstacles, this study aims to analyze the quality of service for permits to operate private education units through the SiCantik Cloud application. This type of research is descriptive with a qualitative approach. The focus of this research uses the theory of Measuring the quality of e-government from the user perspective by Kozak (2018). Data collection techniques through interviews, observation, and documentation. The results showed that in the ease of use indicator, it can be easily accessed in search engines supported by URLs that are easy to remember. Indicators of content and appearance of the information, SiCantik Cloud has an attractive appearance and is easy to understand and consists of several features. Reliability indicators, SiCantik Cloud is considered to have provided convenience for users, but there are obstacles experienced, namely applications that often error, slow loading and usernames and passwords that are not sent to user email. Citizen support indicators, the SiCantik Cloud application does not yet have an FAQ. In the trust/security indicator, DPMPTSP Gresik Regency guarantees the security of user data. Indicators of support in completing forms, SiCantik Cloud supports automatic form filling. Suggestions given include increasing the socialization of SiCantik Cloud, improving the download feature and adding an FAQ feature.